Menanti Kehadiran Pengadilan Khusus Pilkada - Ibnu Affan (Universitas Islam Sumatera Utara, 2018)
According to the 1945 Constitution, Pilkada is not an electoral regime, but it is included in the regime of local government. Therefore, the addition of the Constitutional Court's authority to adjudicate cases of election result disputes is unconstitutional. Decision of the Constitutional Court Number 97/PUU-XI/2003 read out on May 19, 2014 has canceled the Constitutional Court's authority to resolve election disputes. In its decision the Constitutional Court declared that Article 236C of Law no. 12 Year 2008 on Regional Government and Article 29 paragraph (1) letter(e) of Law no. 48 Year 2009 on Judicial Power is declared contradictory to Article 18 and Article 22E of the 1945 Constitution and has no binding legal force. Furthermore to resolve election disputes formed special court as regulated in Law no. 10 of 2016 on the Second Amendment to Law Number 1 Year 2015 Concerning the Stipulation of Government Regulation in Lieu of Law No. 1 of 2014 on the Elections of Governors, Regents, and Mayors Becoming Laws.